Moderasi Beragama dan Relevansinya Dengan Pendidikan Islam Perspektif M. Quraish Shihab - Anis Sulistyarini; Ach Khusnan (Jurnal Pendidikan Agama Islam Miazhar, 2022)
Indonesia is a country that has a rich diversity of cultures, ethnicities, races and languages. This diversity has become an identity for the Indonesian nation which is a great potential for the Indonesian state to have various groups of citizens with different customs, cultures and mindsets as well.So that self-awareness is needed from each individual or group that difference is a gift given by Allah SWT which is used as a place to complement each other.Lately, the understanding of radical Islam has become stronger, which is marked by the many cases of intolerance in the name of religion.Acts of extremism in the name of religion often occur in Indonesia. Incidents of suicide bombings, carrying out anarchist acts against groups that do not agree, destroying places of worship of people who are carrying out worship are forms of action that according to them are forms of fighting or jihad in the way of religion. In fact, this action indirectly caused chaos, unrest and many victims fell.In this study, we wanted to find out about the moderation of religion from the perspective of M. Quraish Shihab and its relevance to Islamic education. Therefore, the right method to use is library research.This research was conducted using primary data sources, namely a book by M.Quraish Shihab entitled "Wasathiyyah Islamic Insights About Religious Moderation" and two books entitled "Tolerance" and "Islam and Nationality".To obtain the necessary data the researcher reads, observes, identifies, classifies and describes the explanation of religious moderation in the Wasathiyyah book.The data analysis technique used is content analysis. Content analysis technique is an in-depth study of the content of written or printed information in the mass media.The research that has been done shows that religious moderation according to M. Quraish Shihab contains five important pillars, namely balance, justice, tolerance, taking the middle way, and deliberation. This pillar is contained in the content of Islamic religious education books in grades VIII to XII at the junior high school to high school education levels which are studied by students in Islamic religious education subjects. .